Природне відновлення і динаміка чисельності деревних видів дендропарку “Тростянець” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The role of natural renewal in dynamics of an total numbers of wood species of park plantings is investigated. It is shown the participation of the separate autoregnerative species in this dynamics and character of distribution of renewing plants in the pregenerative stage of the ontogenesis on territory of the park, depending on the existing phytocenotical situation. The results of researches may matter from the point of view of understanding of the development processes of the park cenosises and give an opportunity of their purposeful correction.